Analisis kecerdasan logis matematis peserta didik kelas V dalam menyelesaikan soal cerita matematika - Petrus Rinto Jati Nugroho; Joko Daryanto; Sandra Bayu Kurniawan (Universitas Sebelas Maret, 2024)
Abstract. Abstract. The purpose of this research is to describe the mathematical logical intelligence of fifth-grade students in solving word problems on the topic of Volume at SD Negeri Rejosari 01. The study used a qualitative descriptive approach to analyze the data of students' mathematical logical intelligence levels with 17 student subjects through document studies, teacher interviews, and student interviews. Data validation was done using the triangulation technique. The data analysis technique used three simultaneous activities: data reduction, data presentation, and data conclusion/verification. The results showed that students with high mathematical logical intelligence were able to perform mathematical calculations, solve problems, use inductive and deductive reasoning, recognize patterns in information and data, but still did not fully meet the ability to think logically optimally. Students with moderate mathematical logical intelligence were able to perform mathematical calculations but were lacking in other aspects. Students with low mathematical logical intelligence almost did not meet any of the mathematical logical intelligence abilities optimally.